1990
DOI: 10.1016/s0022-5347(17)39970-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Transferrin Receptor Content in Human Prostate Cancer Cell Lines Assessed in Vitro and in Vivo

Abstract: Transferrin receptors (TfR) were measured in benign and malignant prostatic cells by performing Scatchard analysis following the administration of 125I-transferrin. Established human prostate cancer cell lines (PC-3 and DU-145) as well as biologically aggressive variants (PC-3 ASC and PC-3 DES) were shown to possess significant levels of high affinity TfR when assessed in vitro. In contrast, TfR content was negligible in cultured stromal cell fractions derived from human benign prostatic hyperplasia (BPH) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 25 publications
3
51
0
1
Order By: Relevance
“…We have previously reported that the addition of the transferrin (Tf) ligand to a cationic liposome com plex resulted in an in vitro transfection efficiency of 70-80% in squamous cell carcinoma of the head and neck (SCCHN) as compared with only 5-20% transfection by the cationic liposome com plex without Tf (L. . Transferrin receptor (TfR) levels are known to be elevated in various types of cancer cells including breast (Inoue et al, 1993) and prostate cancers (Keer et al, 1990), even those prostate cancer cell lines derived from human lym ph node and bone metastases (Grayhack et al, 1979;Chackal-Roy et al, 1989;Rossi and Zetter, 1992), as well as squam ous cell carcinomas (Thorstensen and Romsio, 1993;Miyamoto et al, 1994), and correlate with the aggressive or proliferative ability of tumor cells (Elliott et al, 1993).…”
Section: Introduction Wmentioning
confidence: 99%
“…We have previously reported that the addition of the transferrin (Tf) ligand to a cationic liposome com plex resulted in an in vitro transfection efficiency of 70-80% in squamous cell carcinoma of the head and neck (SCCHN) as compared with only 5-20% transfection by the cationic liposome com plex without Tf (L. . Transferrin receptor (TfR) levels are known to be elevated in various types of cancer cells including breast (Inoue et al, 1993) and prostate cancers (Keer et al, 1990), even those prostate cancer cell lines derived from human lym ph node and bone metastases (Grayhack et al, 1979;Chackal-Roy et al, 1989;Rossi and Zetter, 1992), as well as squam ous cell carcinomas (Thorstensen and Romsio, 1993;Miyamoto et al, 1994), and correlate with the aggressive or proliferative ability of tumor cells (Elliott et al, 1993).…”
Section: Introduction Wmentioning
confidence: 99%
“…Furthermore, Ti(IV) from titanocene dichloride rapidly binds to Tf (6). Moreover, Ti(IV)-bound Tf (Ti 2 -Tf) is thought to specifically target cancer cells because some cancer cells express higher levels of Tf receptors (12). Ti 2 -Tf binds with high affinity to Tf receptor 1 (TfR1) (13), and it has also been shown to block Fe(III)-bound Tf (Fe 2 Tf) from entering a placental cancer cell line (6).…”
mentioning
confidence: 99%
“…The enhanced gene transfection induced by transferrin coupled to liposomes is a typical example of ligand-mediated gene delivery. 29,30 Specific antibodies can also be attached to liposomal surfaces, enabling them to be directed to selected tumorcell surface antigens. [31][32][33] It has been reported that anti-HER-2 monoclonal antibody Fab 0 fragments conjugated to liposomes bind specifically to breast cancer cell line SK-BR-3 overexpressing the HER-2/neu (EFG receptor), resulting in enhanced internalization of the liposomes.…”
Section: Discussionmentioning
confidence: 99%